Comparative Evaluation of Seven Tigecycline Susceptibility Testing Methods for Carbapenem-Resistant Enterobacteriaceae - Li, Hongling (Infect Drug Resist, 2021)
PURPOSE: Carbapenem-resistant Enterobacteriaceae (CRE) strains are extensively resistant to most antibiotics. Tigecycline is one of the few effective drugs that can be used to treat infections caused by CRE. The aim of this study was to evaluate the accuracy of different methods for detecting the susceptibility of CRE to tigecycline. METHODS: Seven commonly used drug susceptibility testing methods were compared and evaluated for the ability to determine CRE tigecycline susceptibility: broth microdilution (BMD), agar dilution method (ADM), disk diffusion method, Etest, MicroScan, Vitek2 COMPACT, and BD Phoenix 100. RESULTS: The minimum inhibitory concentration (MIC) of tigecycline to inhibit 50% and 90% of CRE growth (MIC(50) and MIC(90), respectively) assessed by ADM and BD Phoenix 100 was the same as that determined by the reference method, BMD. The MIC(50) was 2 µg/mL, and the MIC(90) was 4 µg/mL. The highest number of susceptible strains was detected by MicroScan, followed by BMD, Etest, ADM, BD Phoenix 100, Vitek2 COMPACT, and disk diffusion method, in descending order. No significant differences were observed among the tigecycline susceptibility results (P > 0.05) obtained from MicroScan, Etest, BD Phoenix 100, and BMD. BMD confirmed that 82.0% of strains were susceptible to tigecycline. ADM, MicroScan, and BD Phoenix 100 yielded the categorical agreement of 96%, 92%, and 93%, respectively. No method was found to present any very major errors (VMEs), and only the Vitek2 COMPACT yielded major errors (MEs) greater than 3%. CONCLUSION: Among the seven methods tested, the ADM, MicroScan, and BD Phoenix 100 methods were accurate for determining the tigecycline susceptibility of CRE. MicroScan was acceptable with better performance than other methods.